Cracking a Ph. D. : revelation of 5 stages in doctoral journey. - Lindawati (Springer, 2017)
This book offers valuable insights into completing your Ph. D., and subsequently finding and excelling at a job. Further, it highlights other opportunities that a Ph. D. can offer, aside from the research and academic aspects. The book focuses on the five stages that PhD candidates normally go through: joining a Ph. D. programme, starting a PhD course, conducting research, writing their dissertation and finally, looking for the ideal job. Serving as an extensive "cheat sheet", it explains the options and choices that need to be made to join and complete a Ph. D. programme; setting expectations; selecting a research topic; celebrating the completion of a Ph. D. programme, and most importantly, how one can continue to develop after its completion. With a bonus chapter in each stage that describe the perspectives and expectations from different people or organizations, this book shares vital lessons, showing readers how to apply them to a range of situations to create a successful Ph. D. ecosystem.
Keywords: Doctor of philosophy degree.; elektronické knihy; electronic books